Chernobyl dreams: investigating visitors’ storytelling in the Chernobyl exclusion zone - Ojala, Veera (Emerald Pulishing, 2022)
Purpose
Little is known about the overall meaning of the Chernobyl exclusion zone (CEZ) from the visitors’ point of view. Conceptualizing the zone as a storyscape and its narratives as intangible heritage resources, this study aims to investigate the visitors’ engagement with these resources and the resulting articulations from the engagements as translated into verbal and visual storytelling.
Design/methodology/approach
Participant observation and participant generated images in combination with in-depth interviews with different types of tourists were conducted. This paper uses the photographs chosen by the interviewees themselves as a photo essay to explore the evocation of stories through narrative engagement.
Findings
Through participant-oriented research, this study identified three dominant storytelling themes through which visitors focus their understanding of the CEZ. Visitors’ narrative engagements and visual storytelling co-produce the site and entail fluid and even conflicting narrative articulations about the CEZ and its cultural significance.
Research limitations/implications
The discoveries of this study stem from a unique developing heritage site. This study provided a more nuanced understanding of the different visitor categories in the CEZ and their group-specific ways to articulate, imagine and co-produce the storyscape of Chernobyl.
Originality/value
Gaining insight into the verbal and visual storytelling of tourists will contribute to the discussion of narrative consumption of different consumption profiles in tourism sites in addition to the mediation and construction of entangled memory spaces.